Dual-Language Programme in Malaysian secondary schools: glancing through the students’ readiness and unravelling the unheard voices - Ashairi Suliman,; Mohamed Yusoff Mohd Nor,; Melor Md Yunus, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Learning Science and Mathematics in English has its own advantages and disadvantages. Since the abolishment of English for Teaching Mathematics and Science policy (PPSMI), the Ministry of Education has introduced an initiative named the Dual-Language Programme (DLP) in 2016. This study aims to identify the level of readiness and confidence among the students in this programme. In tandem, it also aims to discover the difference in the level of readiness between Form One and Form Two DLP students as well as gender influence. Respondents were 145 DLP students comprising 80 Form One and 65 Form Two students. This study employed five-point Likert scale questionnaire as the instrument and open-ended questions to validate the findings. From the data analysis generated by SPSS 19, the level of readiness and confidence among the DLP students was moderate. The findings further revealed that there was no significant difference concerned between the variables, class and gender. English language mastery was found to be one of the main factors influencing the students’ readiness towards this programme. To sum up, the DLP is a positive move put forward by the government aimed at valorising the standard of English among the students via the learning of Science and Mathematics. However, more initiatives and efforts are deemed essential to the execution of the DLP towards progressivism.